(3GfYcGSGJ GdeJZjQGJ GdeYGUQI Ydj GdbWGY GdeUQaj hOhQ GdHfhc GdeQcRjI (B:s (3OQGSI JMdjdjI(B-(3JWHjbjI dMGdGJ eNJGQI ef GdHdOGf GdYQHjI (B/s - (3eMeO Ydj, GMeO TYHGfs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2007)
(3eGgjI GdHfhc GdeQcRjI , GdeJZjQGJ GdGbJUGOjI GdeYGUQI hGdGbJUGO GdYGdej GdeJZjQGJ GdGbJUGOjI GdeYGUQI , GfYcGSGJ GdeJZjQGJ GdGbJUGOjI Ydi GdGbJUGO GdYGdej , GdSjGSI GdfbOjI aj Xd XQha GdGbJUGOjGJ GdeJbOeI hGdfGejI , JWhQ COGA GdHfc GdeQcRj hOhQg aj GdHdOGf GdYQHjI , GdJhGab eY HGRd (B2 (3hOhQ GdHfhc GdeQcRjI GdJhLgGJ GdYGeI ddLfI HGRd ddQbGHI GdeUQajI , JaYjd GdJYGhf eY GdHfhc GdeQcRjI aj GdHdOGf GdYQHjI , COGA GdHfhc GdeQcRjI GdYQHjI fehPL bjGSjs
(3HjHdjhZQGajG U(B.383 (3edGMb U(B.510s
Keywords: (3GdGfJGLs; (3GdHfhc GdeQcRjIs; (3GdbWGY GdeUQajs; (3GdeJZjQGJ GdGbJUGOjIs